THE IMPLEMENTATION OF 2013 CURRICULUM AT ELEMENTARY SCHOOL - Susilana, Rudi (Prodi Teknologi Pendidikan, 2015)
Abstract. The implementation of the new 2013 Curriculum in schools has been started in July 2013. The implementation of the curriculum is expected to increase the quality of management and process of education at any unit of education that leads to the effort of improving the quality of learning and education. In connection with the application of the new curriculum, this research would like to reveal the problems regarding how elementary school teachers respond to the implementation of 2013 Curriculum in Bandung City with regard to planning, implementation, and assessment of curriculum. It also studied the best practice which can be emulated in terms of planning, implementation and assessment of curriculum conducted by elementary school teachers in Bandung City.The results showed that the response of elementary school teachers on the implementation of 2013 Curriculum in Bandung City was in the positive category. The planning activity was in the category of very positive while the implementation and assessment activities were in the positive category. Some best practices that can be emulated in planning, implementation and assessment conducted by the teachers in implementing the 2013 Curriculum are the activities of sharing, hearing, in-house training and real teaching modeling that were carried out in Teacher Working Group (KKG).Keywords: 2013 Curriculum, teachers’ response, best practice, curriculum implementation Abstrak. Penerapan kurikulum baru, yakni implementasi Kurikulum 2013 di sekolah telah dimulai sejak bulan Juli 2013. Implementasi Kurikulum tersebut diharapkan mendorong peningkatan kualitas pengelolaan dan proses pendidikan pada setiap satuan pendidikan yang mengarah pada upaya peningkatan mutu pembelajaran dan pendidikan. Dilatarbelakangi oleh adanya penerapan kurikulum tersebut, penelitian ini ingin mengungkap permasalahan yang berkenaan dengan